Analyzing data using transana software for interaction in computer support face-to-face collaborative learning (cosofl) among esl pre-servive teacher - Salam, Abdul Rahim; Tasir, Zaidatun; Abdul Samad, Adlina (2008)
This paper presents the researcher’s experience using Transana software as a tool for analyzing knowledge construction among ESL pre-service teacher. It was used in the pilot study to assist the qualitative data analysis. Data analyzed was based on face-to-face peer responses supported by computer collaborative technology with a group of students enrolled in Microteaching course at the Faculty of Education, University Technology Malaysia. The Transana software was explored to see whether it could facilitate the analysis of COSOFL verbal interaction . This paper briefly narrates the researcher experience in making use of the software to analyse the interaction. The analysis relied on the use of Mp3 recordings. The software helped in identifying and organizing analytically interesting portions of the recording, as well as in attaching keywords to the digitized data recordings. This software allowed the verbal recordings to come out in line with the transcription for the purpose of easy management in transcribing, coding, and analyzing verbal response among peers. Selected data from the pilot study will be shown to illustrate the use of Transana software.